Formation of Independent and Responsible Attitudes Through the Application of the Sociodarm Method in PPKn Learning in Elementary Schools - Rahmadana, Nadila Okta (International Journal of Students Education, 2024)
Civic education is Continuous Subjects adapt with development era. This lesson covers various global issues such as identity, dependency, morality, culture, ethnicity, religion, rights, and not quite enough Responsible. Responsibility responsibility and independence is matter important things to do instilled in the generation young so that they can face change era.Strengthening attitude independent and responsible answer can done through method role - focused learning active students,work groups, as well as breakdown problem. Research purposes this is for describe about method apply method learning sociodrama in learning citizenship education in elementary school and how to to form attitude independent and responsible answer through learning sociodrama. This description given so that teachers can apply method the with good in the classroom so that attitude independent and responsible answer can formed in self participant educate the role of teachers in implement formation attitude independent and responsible answer with apply method sociodrama use text for influence significant to attitude not quite enough responsibility and achievement study student.